2020
DOI: 10.1177/2045894019898030
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone in pulmonary arterial hypertension: results of a cross‐over study

Abstract: The renin–angiotensin–aldosterone system is implicated in the pathophysiology of pulmonary arterial hypertension. We undertook this study to determine the effects of spironolactone, a mineralocorticoid receptor blocker, on collagen metabolism in pulmonary arterial hypertension patients. After obtaining institutional review board approval and informed consent, 42 pulmonary arterial hypertension patients were prospectively enrolled and 35 patients completed the 16-week randomized double-blinded crossover clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…During this time, the expression of TIMP-1 and TIMP-2 are also up-regulated to inhibit excessive MMP activity through a balancing mechanism [ 39 ]. However, since the balancing effect is limited, the ratio of MMP-9/TIMP-1 and MMP-2/TIMP-2 is elevated, which contributes to excessive ECM accumulation and the development of PAH [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…During this time, the expression of TIMP-1 and TIMP-2 are also up-regulated to inhibit excessive MMP activity through a balancing mechanism [ 39 ]. However, since the balancing effect is limited, the ratio of MMP-9/TIMP-1 and MMP-2/TIMP-2 is elevated, which contributes to excessive ECM accumulation and the development of PAH [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mineralocorticoid receptor (MR) blocker spironolactone has antifibrotic properties and has shown to be beneficial in patients with systolic left heart failure. Spironolactone is frequently used as a diuretic in PAH [ 42 ].…”
Section: Potential Pharmacological Actions Of Spironolactone In Comentioning
confidence: 99%
“…No change in walk distance was noted at weeks 8 and 16. 299 A post-hoc study from ARIES 1 and ARIES 2 clinical trials indicated some positive effects in the addition of spironolatone to ambrisantan. 300 Subsequently, a prospective study examined in 30 subjects with PAH, the effect of spironolactone when added to ambrisentan on exercise capacity (NCT02253394).…”
Section: Aldosterone Antagonistmentioning
confidence: 99%